Comparative metabolomic analysis of the body wall from four varieties of the sea cucumber Apostichopus japonicus. (1st August 2021) - Xing, Lili; Sun, Lina; Liu, Shilin; Zhang, Libin; Yang, Hongsheng
Highlights: Differential metabolite and pathway of four A. japonicus varieties were identified. Fatty acids, phospholipids and sugars were important in differentiating varieties. Carbohydrate, protein and phospholipid metabolism were conserved among varieties. Body wall metabolic profiles could be discriminated clearly according to varieties. Abstract: The sea cucumber, Apostichopus japonicas, is an important economic species with high nutritive value. In recent years, driven by significant market demand, the sea cucumber breeding industry has developed rapidly. Body color and number of papillae are important factors that determine the value and price of sea cucumbers. In this study, metabolite profiling of four sea cucumber varieties (green, white, purple and spiny) was performed using ultra-performance liquid chromatography-quadrupole-time-of-flight-mass spectrometry (UPLC-QTOF-MS) combined with multivariate analysis. Orthogonal partial least-squares discriminant analysis (OPLS-DA) clearly discriminated the body wall metabolites of four sea cucumber varieties. Differential metabolites included fatty acids, phospholipids, and sugars. KEGG metabolic pathway analysis revealed that carbohydrate, protein, and phospholipid metabolism were highly conserved among the varieties. These results provide a comprehensive insight into differences in the metabolite profile of four A. japonicus varieties and a deeper understanding of sea cucumber varieties breeding.